Examining the Impact of Availability and Accessibility of Community Benefit Provisions on County Health Outcomes - Cha J; Han A; Lee KH (Risk Management and Healthcare Policy)
Jinyoung Cha,1 Ahreum Han,2 Keon-Hyung Lee1 1The Askew School of Public Administration and Policy, Florida State University, Tallahassee, FL, USA; 2Department of Health Care Administration, Trinity University, San Antonio, TX, USACorrespondence: Keon-Hyung Lee, Email klee2@fsu.eduBackground: The recent rise of accountability in healthcare providers has spurred a keen interest in improving community benefit provisions and how these are associated with community health development. However, prior studies predominantly focus on the adequate amount of community benefit provisions (availability), disregarding the potential influence of distributional provisions (accessibility). To fill this gap, this study explores how the total amount (availability) and Blau’s Index (accessibility) of community benefits are positively associated with county health outcomes.Methods: This study adopts a cross-sectional time series two-way fixed effect analysis from 2014 to 2019 for the county level. Independent variables are calculated as the total amount and Blau’s Index of community benefit provisions in hospital referral regions (HRRs). Dependent variables are county health outcomes, measured by physical and mental unhealthy days and distress days.Results: The results demonstrated that both the availability and accessibility of community benefit provisions are correlated with lower physical and mental healthy days and distress. Remarkably, the accessibility of community benefit provisions by hospitals became pivotal to improving county health outcomes.Conclusion: From the theoretical aspects, it provides empirical evidence between community benefit provisions and community health outcomes and extends the theory of access into community benefit provisions. From the practical aspects, it offers invaluable insights for hospital managers and policymakers for their strategic decision-making to contribute to community health outcomes.Keywords: community benefit provisions, theory of access, county health outcomes